2016
DOI: 10.1016/j.ejca.2016.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Needle biopsy through the abdominal wall for the diagnosis of gastrointestinal stromal tumour – Does it increase the risk for tumour cell seeding and recurrence?

Abstract: Purpose: Preoperative percutaneous transabdominal wall biopsy may be considered to diagnose gastrointestinal stromal tumour (GIST) and plan preoperative treatment with tyrosine kinase inhibitors when an endoscopic biopsy is not possible. Hypothetically, a transabdominal wall biopsy might lead to cell seeding and conversion of a local GIST to a disseminated one. We investigated the influence of preoperative needle biopsy on survival outcomes. Methods: We collected the clinical data from hospital case records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 8 publications
(14 reference statements)
2
29
0
1
Order By: Relevance
“…This patient had a simple resection with iatrogenic peritoneal laceration for a jejunal tumour and was disease‐free at 69 months with no adjuvant therapy. In the SSG XVIII/AIO trial, CNB was not considered rupture, and recurrences were not increased in patients who were submitted to it. A growing body of evidence indicates that CNB can be performed without risk in abdominal and retroperitoneal sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…This patient had a simple resection with iatrogenic peritoneal laceration for a jejunal tumour and was disease‐free at 69 months with no adjuvant therapy. In the SSG XVIII/AIO trial, CNB was not considered rupture, and recurrences were not increased in patients who were submitted to it. A growing body of evidence indicates that CNB can be performed without risk in abdominal and retroperitoneal sarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Current biopsy techniques include image guidance and the use of coaxial needles to minimize this risk. A systematic evaluation of the SSG XVIII/AIO trial comparing 1 and 3 years of adjuvant imatinib in high-risk GIST was performed to determine the rate of biopsy-associated recurrences [48]. Analysis of 397 patients of whom 47 underwent percutaneous biopsy revealed that there was no difference in the recurrence rates between the two groups.…”
Section: Preoperative Treatment Of Locally Advanced Gistmentioning
confidence: 99%
“…However, it is limited to the lumen of the digestive tract where EUS is available, and the pathological diagnosis is sometimes difficult because of the small amount of tissue obtained. Western guidelines recommend fine needle biopsy through the abdominal wall based on the results from retrospective studies (SSG-AIO XVIII), indicating that such biopsies did not increase the recurrent risk when appropriate surgery and/or medical therapy were done after biopsy [31]. …”
Section: Surgical Treatment Of Gistsmentioning
confidence: 99%